Recreational use of urban green space in Malaysian cities - Abdul Aziz, Nor Akmar; Cecil Konijnendijk van den Bosch; Nillson, Kjell (Universiti Malaysia Sarawak, 2018)
To support green space provision and management, it is important to obtain accurate information about the recreational use of green space, regarding use frequency and types of use, visiting time and duration of visits, but also on how the characteristics of different users influence these. Although these studies have become more common in developed countries, developing countries are lagging behind. In Malaysia, major cities such as Kuala Lumpur (Peninsular Malaysia) and Kuching (Sarawak) have experienced growth and policy makers recognise the importance of their green spaces, but lack comprehensive user studies. This paper presents the results from a comparative study on the use of green spaces and visitor preferences for five selected parks in Kuala Lumpur and Kuching. The study comprised, among others, a survey among residents living within a two kilometre radius of the park boundaries. A total of 1,692 respondents answered the questionnaire. Results show that close to 9 out of 10 people living within a 2 km radius of the studied parks use them for recreational purposes. Most of the respondents visit the parks during weekends and typically travel by car, in spite of the short distance to the park. The study also identified differences in green space usage patterns according to different socio-demographic and economic factors, including ethnicity. Malaysians of Chinese descent, for example, have a greater preference for using parks during the morning compared to Malaysians of Malay and Indian descent. Differences were also found regarding motivations for using the parks. However, various similarities can also be noted, e.g. regarding length of use visiting together with family members. It is important for park management to recognise park use patterns and preferences, in particular also where different groups are concerned.